2021
DOI: 10.1200/jco.2021.39.15_suppl.6535
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Telehealth services for cancer care at cancer hospital in the United States.

Abstract: 6535 Background: The COVID-19 pandemic has dramatically accelerated the availability of telehealth services for patients with cancer. However, little national cross-sectional data is available to inform potential gaps in access. We aimed to characterize overall access to and trends in telehealth availability for new cancer care patients at hospitals across the United States. Methods: We performed a cross sectional secret-shopper study to evaluate the availability of telehealth services for new patients for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This future analysis is required, as previous work has suggested that marginalized patients participate in video visits less often than nonmarginalized peers due to limitations of technological access and literacy [ 15 ]. Second, we found differential access to and use of email and VC by clinic type, echoing findings of other studies [ 16 ]. While differential VC use by clinic type may be attributable to clinical reasoning regarding the added benefit of in-person oncologic assessment to VC-amenable biochemical and/or radiographic surveillance in certain clinical contexts, differential access to email and survey responsiveness by clinic type are agnostic to provider preferences and may be indicative of unaccounted intersectional digital divides among subpopulations with lower socioeconomic status [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This future analysis is required, as previous work has suggested that marginalized patients participate in video visits less often than nonmarginalized peers due to limitations of technological access and literacy [ 15 ]. Second, we found differential access to and use of email and VC by clinic type, echoing findings of other studies [ 16 ]. While differential VC use by clinic type may be attributable to clinical reasoning regarding the added benefit of in-person oncologic assessment to VC-amenable biochemical and/or radiographic surveillance in certain clinical contexts, differential access to email and survey responsiveness by clinic type are agnostic to provider preferences and may be indicative of unaccounted intersectional digital divides among subpopulations with lower socioeconomic status [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…Some have noted the potential benefits of VC and email for enhancing equitable care [10][11][12], including increased health care utilization among racialized minorities and those with travel restrictions. Others have expressed concerns about digital divides in access to VC due to structural marginalization [13][14][15][16][17], particularly among marginalized populations known to be more prone to adverse oncologic outcomes [18,19]. These concerns underscore the importance of investigating inequities following the adoption of digital health tools and addressing their impact on oncologic care [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Rates of telemedicine use varied across oncology subspecialties, ranging from 38% in breast oncology to 47% for cutaneous oncology. 34 Specialties such as cardiology, gastroenterology, and neurology that often help manage novel therapies and their toxicities also experienced substantial increases in virtual care. While rates of telemedicine use have declined some since the beginning of the pandemic, they remain higher than prepandemic levels.…”
Section: Virtual Care During Covid-19mentioning
confidence: 99%
“…A 2020 survey of oncology practices showed that 100% of National Cancer Institute–designated cancer centers and 61% of community practices offered virtual visits. Rates of telemedicine use varied across oncology subspecialties, ranging from 38% in breast oncology to 47% for cutaneous oncology 34 . Specialties such as cardiology, gastroenterology, and neurology that often help manage novel therapies and their toxicities also experienced substantial increases in virtual care.…”
Section: Virtual Care During Covid-19mentioning
confidence: 99%